PENGGUNAAN MEDIA INTERAKTIF BAAMBOOZLE TERHADAP MOTIVASI BELAJAR SISWA SEKOLAH DASAR - Andriyani, Yunita; Nurlinda Safitri; Yuyun Yuniar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to describe the use of Baamboozle interactive media on elementary school students' learning motivation. Using a descriptive qualitative research method, the research subjects consisted of teachers and fourth grade students at SDN Panaragan 1. The research instruments included interviews, observations, and documentation to obtain data on the experiences and views of the subjects related to the use of Baamboozle in the learning process. The results showed that the use of Baamboozle significantly increased students' learning motivation. Students involved in learning with Baamboozle showed higher enthusiasm, were more active in learning activities, and participated more often in group discussions. This media also provides a more interactive learning experience, makes it easier to understand the material, and supports the concept of game-based learning which has been proven to increase students' interest and motivation. Baamboozle not only makes learning more interesting and fun, but also encourages students to think critically and develop analytical skills.